2013
DOI: 10.1097/ajp.0b013e31827eafff
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous and Perineural Botulinum Toxin Type A For Neuropathic Pain

Abstract: On the basis of the analysis of the reports published in the literature, it would seem that fractioned peripheral subcutaneous and perineural injections of botulinum toxin type A may be useful for the treatment of various chronic pain conditions with neuropathic component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
0
19
0
3
Order By: Relevance
“…[31,32] Its pain relief effect might be mediated through the sensory system. [27] The dosage of BTA previously used for treating neuropathic pain was between 2.5 and 7.5 U/cm 2 at each painful surface area with the maximum total dosage from 100 to 200 U.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] Its pain relief effect might be mediated through the sensory system. [27] The dosage of BTA previously used for treating neuropathic pain was between 2.5 and 7.5 U/cm 2 at each painful surface area with the maximum total dosage from 100 to 200 U.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have reported that BTX‐A for the treatment of neuropathic pain can be administered subcutaneously or intradermally 9, 10, 11, 25, 26. The effects on pain may be mediated through direct effects on the sensory system 16.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous case report of BTX for neuropathic pain in patients with spinal cord lesions, BTX‐A was administered subcutaneously; a subcutaneous route was chosen for this study 17. In most studies, the fractioned dosage of BTX‐A for the treatment of neuropathic pain was between 2.5 and 7.5U/cm 2 per painful surface area, and the maximum total dosage was between 100 and 200U 9, 10, 11, 25, 26, 27. In the present study, the painful surface area in patients with SCI was generally larger than that in patients with focal neuropathy such as postherpetic neuralgia and post‐traumatic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…A cadeia leve vai exercer uma atividade proteolítica sobre o complexo SNARE, indispensável para a fusão de vesículas de acetilcolina com a membrana pré-sináptica. 4,18,16 A toxina, de acordo com seu sorotipo, vai quebrar uma ou outra proteína deste complexo (no caso da BTX-A a SNAP 25), e tem como consequência a inibição da translocação, exocitose e liberação de acetilcolina na fenda sináptica. 16,18 Inicialmente, acreditava-se que as propriedades analgésicas da BTX-A estavam associadas à diminuição da contração muscular e provavelmente associada a suas propriedades colinérgicas.…”
Section: Uso Da Toxina Botulínica Na Neuralgia Pós-herpéticaunclassified
“…24 Na maioria dos estudos, BTX-A foi administrada por via subcutânea ou intradérmica com doses fracionadas variando de 2,5 a 7,5 UI/ cm 2 na área dolorosa, não sendo ultrapassadas 200 UI no total. 3,18 Em teoria, a toxina botulínica tem potenciais vantagens quando comparada a analgésicos orais, seja por sua longa duração de ação (aproximadamente três meses), pela facilidade de ser administrada diretamente no ponto doloroso, por sua excelente tolerabilidade, seja por seu perfil de segurança e ausência de efeitos sistêmicos. 25 …”
Section: Técnica De Aplicaçãounclassified